Stabilitas Tanah Plastisitas Tinggi Dengan Semen - Roni Indra Lesmana; Muhardi Muhardi; Soewignjo Agus Nugroho (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Ground high plasticity have the properties is bad so do not meet the technical requirements desired. The properties owned land in the form of low bearing capacity, compression (compressibility) high, sweilling large, and difficult to carry out the work of compaction, it is necessary for the stabilization of the soil. One of the ways used to solve problems among other things stabilized with cement. The purpose of this study to determine the effect of OPC cement type or PCC at high plasticity ground against the carrying capacity of land, CBR and UCS. Testing was conducted on the physical and mechanical properties of soil, compaction parameters, CBR and UCS. The standard test used is ASTM. Variations cement used is the addition of 6%, 8%, 10% for each OPC cement and PCC. Curing is done before the test CBR and UCS, the curing time for 28 days on the condition of optimum water content. Results from the study showed that the increase in the maximum CBR value occurs in a mixture of 10% which is 139.70% to 116.43% OPC and for PCC. The maximum value of UCS also occur on the addition of cement by 10%. In the cement mixture with OPC, qu max by 1.44 MPa and 2.43 MPa with a mixture of cement PCC.Keywords: curing, high plasticity, stabilization, cement